MENGANTISIPASI POTENSI BANJIR: PARTISIPASI TIM PPM FIB UNPAD DALAM NORMALlSASI SUNGAI CIKERUH DI DESA CIKERUH KECAMATAN JATINANGOR KABUPATEN SUMEDANG - Sofianto, Kunto; Mahzuni, Dade; Koeshandoyo, Eko W.; Gustaman, Budi; Falah, Miftahul (Unpad Press, 2026)
The problem underlying this Community Service Program (Pengabdian pada Masyarakat/PPM) is the disaster vulnerability of Cikeruh Village, Jatinangor Subdistrict, Sumedang Regency, which is prone to flooding during every rainy season due to sedimentation and pollution of the Cikeruh River. For this reason, community participation is needed to support the normalization process. The methods applied in this PPM activity include community education and mediation, integrated into a series of stages consisting of education, observation, mediation, and action. In the 2025 PPM implementation, three main efforts were undertaken. First, education and observation were conducted at flood-prone locations to identify the root causes of the problem. Second, mediation was carried out with relevant stakeholders, including village authorities and the community of Cikeruh Village, the Citarum River Basin Authority (Balai Besar Wilayah Sungai/BBWS Citarum), and the Public Works and Housing Agency (Dinas Pekerjaan Umum dan Perumahan Rakyat/PUPR) of Sumedang Regency. Third, active participation was provided in the implementation of river dredging actions carried out by the Public Works and Housing Agency of Sumedang Regency. Overall, this PPM activity is aligned with the vision of the West Java Provincial Government and its affiliated institutions in declaring a commitment to environmental conservation, particularly river preservation, as an effort to strengthen community disaster resilience.